Opening Science: The Evolving Guide on How the Internet is Changing Research, Collaboration and Scholarly Publishing - Bartling, Sönke (Springer Nature, 2014)
Job Careers in Science and Engineering; Computers and Society; Communication Studies; Web 2.0 and interoperability; Scientific micro blogging; Social networking platforms; Creative commons; Dynamic publication formats; Scientific intellectual property; Collaborative work; Scientific wiki; Open source science; Open data